2018
DOI: 10.37266/iser.2018v6i1.pp21-40
|View full text |Cite
|
Sign up to set email alerts
|

Usability Evaluation of Mobile Weather Hazard Alert Applications

Abstract: Cell phones enable us to receive and respond to critical incidents, such as: severe storms, tornadoes, and flash floods. However, due to the small display size of cell phones, and regardless of simplified symbols or alert messages, it is possible to overlook users’ ability to interact with the available features and understand the messages in a timely manner. Untrained and trained users of the Weather Radio application participated in an experiment to perform three search tasks; (task 1: location search, task … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…First, weather app developers should employ the UCD approach and think of formatting the alert messages from the end-user perspective. Based on the quantitative research findings from Khamaj & Kang (2018), as well as the qualitative research findings presented in this article, the alert messages (that are broadcasted by the NWS to the weather apps) should go through a filtration process before they reach the end-user. Examples of the actions that can be implemented in the filtration process are: 1) removing the geographical area codes for the locations under alerts and including only location names, 2) including information about the user's saved location and the nearby under-alert locations on the main message screen; information regarding all other affected locations could be included on a secondary screen that can be accessed if the user taps a relevant icon from the main message screen, and 3) using appropriate and easy language that considers the differences in users' characteristics (e.g.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, weather app developers should employ the UCD approach and think of formatting the alert messages from the end-user perspective. Based on the quantitative research findings from Khamaj & Kang (2018), as well as the qualitative research findings presented in this article, the alert messages (that are broadcasted by the NWS to the weather apps) should go through a filtration process before they reach the end-user. Examples of the actions that can be implemented in the filtration process are: 1) removing the geographical area codes for the locations under alerts and including only location names, 2) including information about the user's saved location and the nearby under-alert locations on the main message screen; information regarding all other affected locations could be included on a secondary screen that can be accessed if the user taps a relevant icon from the main message screen, and 3) using appropriate and easy language that considers the differences in users' characteristics (e.g.…”
Section: Recommendationsmentioning
confidence: 99%
“…To the best of our knowledge, little work has been done on the usability evaluation of weather apps developed for smartphones. Two recent studies conducted by Khamaj & Kang (2018) and Drogalis et al, (2015) tested the usability of smartphone weather apps using quantitative metrics. The present study aims to add more breadth to the literature and support the findings from previous research by qualitatively investigating users' attitudes, beliefs, and behaviors towards the usability of weather apps.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have focused on age differences in the use of smartphone apps in various fields, including information technology [6], healthcare [7], and communication [8]. However, to our knowledge, there are limited studies on usability testing of weather apps [9,10], and no one has applied user-centered design (UCD) to include a wide range of users, especially elderly. Drogalis et al [10] identified usability issues with weather alert applications, such as the inclusion of hidden map menus that required prior counterintuitive actions and the lack of feedback on actions that were performed.…”
Section: Introductionmentioning
confidence: 99%
“…Drogalis et al [10] identified usability issues with weather alert applications, such as the inclusion of hidden map menus that required prior counterintuitive actions and the lack of feedback on actions that were performed. Khamaj and Kang [9] investigate usability issues such as poor visualization of critical weather information, inappropriate language usage in time-critical alert messages, and inefficient location search functionality. However, neither of the two studies mentioned above addresses the question of how to effectively meet users' issues and needs.…”
Section: Introductionmentioning
confidence: 99%